Combine like terms to create an equivalent expression.
2 answers:
Answer:
2/3q + 7/12
Step-by-step explanation:
Find common Denominator
Common Denominator 12, 6, 3 = 12
Convert Each Term To Have Common Denominator
11/12 - 2/12q + 10/12q - 4/12
Combine Like Terms
11/12 - 4/12 = 7/12
-2/12q + 10/12q = 8/12q → 2/3q
Write Equation
2/3q + 7/12
Answer:
7/12+4/6q
Step-by-step explanation:
You might be interested in
Answer:
Exact form : <u>10√11</u>
Step-by-step explanation:
Answer:
![(2 \times 15x) + (2 \times 10) \\ = 30x + 20 \\ = 10(3x + 2)](https://tex.z-dn.net/?f=%282%20%5Ctimes%2015x%29%20%2B%20%282%20%5Ctimes%2010%29%20%5C%5C%20%20%3D%2030x%20%2B%2020%20%5C%5C%20%20%3D%2010%283x%20%2B%202%29)
Answer:
15
Step-by-step explanation:
Answer:
-12
Step-by-step explanation:
-12/2 = -6
-6+15 = 9
Answer:
X= -3,-5
Step-by-step explanation: